Bacteriophage-Delivering Hydrogels: Current Progress in Combating Antibiotic Resistant Bacterial Infection - Hyun Young Kim; Rachel Yoon Kyung Chang; Sandra Morales; Hak-Kim Chan (MDPI AG, 2021)
Antibiotic resistance remains as an unresolved global challenge in the health care system, posing serious threats to global health. As an alternative to antibiotics, bacteriophage (phage) therapy is rising as a key to combating antibiotic-resistant bacterial infections. In order to deliver a phage to the site of infection, hydrogels have been formulated to incorporate phages, owing to its favorable characteristics in delivering biological molecules. This paper reviews the formulation of phage-delivering hydrogels for orthopedic implant-associated bone infection, catheter-associated urinary tract infection and trauma-associated wound infection, with a focus on the preparation methods, stability, efficacy and safety of hydrogels as phage carriers.